Mechanisms by which Factor H protects Trypanosoma cruzi from the alternative pathway of complement - Menon, Smrithi S.; Ramirez-Toloza, Galia; Wycoff, Keith L.; Ehinger, Sean; Shaughnessy, Jutamas; Ram, Sanjay; Ferreira, Viviana P. (Frontiers in Immunology, 2024)
Chagas disease, a chronic disabling disease caused by the protozoan Trypanosoma cruzi, has no standardized treatment or preventative vaccine. The infective trypomastigote form of T. cruzi is highly resistant to killing by the complement immune system. Factor H (FH), a negative regulator of the alternative pathway (AP) of complement on cell surfaces and in blood, contains 20 short consensus repeat domains. The four N-terminal domains of FH inactivate the AP, while the other domains interact with C3b/d and glycan markers on cell surfaces. Various pathogens bind FH to inactivate the AP. T. cruzi uses its trans-sialidase enzyme to transfer host sialic acids to its own surface, which could be one of the approaches it uses to bind FH. Previous studies have shown that FH binds to complementopsonized T. cruzi and parasite desialylation increases complement-mediated lysis of trypomastigotes. However, the molecular basis of FH binding to T. cruzi remain unknown. Only trypomastigotes, but not epimastigotes (non-infective, complement susceptible) bound FH directly, independent of C3 deposition, in a dose-dependent manner. Domain mapping experiments using 3-5 FH domain fragments showed that domains 5-8 competitively inhibited FH binding to the trypomastigotes by ~35% but did not decrease survival in complement. FH-Fc or mutant FH-Fc fusion proteins (3-11 contiguous FH domains fused to the IgG Fc) also did not kill trypomastigotes. FH-related protein-5, whose domains bear significant sequence identity to all known polyanion-binding FH domains (6-7, 10-14, 19-20), fully inhibited FH binding to trypomastigotes and reduced trypomastigote survival to < 24% in the presence of serum. In conclusion, we have elucidated the role of FH in complement resistance of trypomastigotes.